Dynamic Weighting of Feature Dimensions in Visual Search: Behavioral and Psychophysiological Evidence - Krummenacher, Joseph; Mueller, Hermann J. (Frontiers in Psychology, 2012)
The notion that the neural activations representing a limited set of visual features in the brain are modulated by a process prioritizing a circumscribed part of the visual field has turned out to be a powerful account of selective attention. Extensions of the original approach assuming the existence of feature-based saliency signals governing the allocation of focal attention have recently evolved to explain the spatial and temporal dynamics of the relative strengths of feature-based saliency representations. Here we review recent behavioral and neurophysiological findings providing evidence for the dynamic weighting of feature dimensions in different types of visual search tasks. Inter-trial inhibition and excitation of saliency activation is investigated in feature detection tasks. The redundant signals paradigm is employed to examine the mechanisms of feature integration. The relative significance of dimension-dependent and dimension-independent saliency representations is explored in feature detection and compound search tasks. Visual dimensions, but not spatial locations, modulate search performance in feature and, more pronouncedly, in conjunction search tasks. The influence of features is greatly reduced in compound search. Psychophysiological evidence demonstrates that feature modulation is not affected by response-based processes, even if conditions favor response modulation. Results are interpreted in the framework of the dimension weighting account, a special case of the biased competition hypothesis.